Song of Songs - Hess, Richard S. (Grand Rapids, MI Baker Academic, 2005)
Contents: Prologue : first coming together and intimacy (1:2-2:7) -- Lovers joined and separated (2:8-3:5) -- Love and marriage at the heart of the song (3:6-5:1) -- Search and reunion (5:2-6:3) -- Desire for the female and love in the country (6:4-8:4) -- Epilogue : the power of love (8:5-14). Includes bibliographical references (p. 253-269) and indexes.
Electronic Resource http://www.loc.gov/catdir/toc/ecip052/2004023799.html
Keywords: Bible. O.T. Song of Solomon -- Commentaries